2021
DOI: 10.1186/s13071-020-04554-9
|View full text |Cite
|
Sign up to set email alerts
|

Spatio-temporal analysis of the main dengue vector populations in Singapore

Abstract: Background Despite the licensure of the world’s first dengue vaccine and the current development of additional vaccine candidates, successful Aedes control remains critical to the reduction of dengue virus transmission. To date, there is still limited literature that attempts to explain the spatio-temporal population dynamics of Aedes mosquitoes within a single city, which hinders the development of more effective citywide vector control strategies. Narrowing this knowledge gap requires consist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 25 publications
1
21
0
Order By: Relevance
“…As IIT programs scale up, the ability to maintain suppression over large areas with smaller release numbers is expected to reduce costs, improve sustainability, and minimize inconvenience to residents; avoiding excess release numbers should also reduce the likelihood of Wolbachia establishment due to the smaller number of females inadvertently released ( 33 ). With an effective monitoring system such as a network of traps ( 34, 37 ), programs could transition from regular releases to a risk-based approach, where releases are only performed when and where the vector population exceeds a certain threshold, or where releases are adapted to mosquito trap indices in an operationally manageable manner ( 33 ).…”
Section: Discussionmentioning
confidence: 99%
“…As IIT programs scale up, the ability to maintain suppression over large areas with smaller release numbers is expected to reduce costs, improve sustainability, and minimize inconvenience to residents; avoiding excess release numbers should also reduce the likelihood of Wolbachia establishment due to the smaller number of females inadvertently released ( 33 ). With an effective monitoring system such as a network of traps ( 34, 37 ), programs could transition from regular releases to a risk-based approach, where releases are only performed when and where the vector population exceeds a certain threshold, or where releases are adapted to mosquito trap indices in an operationally manageable manner ( 33 ).…”
Section: Discussionmentioning
confidence: 99%
“…This is not surprising since impervious surfaces are a proxy indicator for urbanization, which provides favourable breeding habitats for Ae. aegypti mosquitoes that thrive in urban environments [46][47]. Next, the transmission intensity of dengue was positively associated with increased proportion of vegetation with structure dominated by human management (without tree canopy).…”
Section: Plos Computational Biologymentioning
confidence: 97%
“…Next, the transmission intensity of dengue was positively associated with increased proportion of vegetation with structure dominated by human management (without tree canopy). This is likely due to the increased availability of water in leaf litter, soil surface, pots and in the discarded receptacles hidden in the foliage or shrub, which supports mosquito breeding [47][48]. In contrast, vegetation with structure dominated by human management (with tree canopy) was associated with lower dengue transmission intensity.…”
Section: Plos Computational Biologymentioning
confidence: 99%
“…Variation in the land use types and vegetation levels surrounding the residential areas surveyed is also likely to have influenced trends in indices between locations [ 34 ]. Previous studies have found that surrounding vegetation types and urbanisation levels to have substantial effects on adult Aedes species abundance, through providing a resting place and sugar source for adults, although the effect can be highly dependent on broader characteristics of the sampling location as well such as human socioeconomic and behavioural factors [ 43 , 44 ]. Each of these influences would be a useful variable to explore in future studies–particularly in the seven locations that consistently recorded above-threshold values in indices across multiple surveys.…”
Section: Discussionmentioning
confidence: 99%